One-step synthesis of fluorine-functionalized intercalated graphene with adjustable layer spacing for both enhanced physical and chemical hydrogen storage - Chaojie Liu; Yongyang Zhu; Anqi Zu; Yike Liu; Zhiyang Zhang; Junjie Guo; Chuo Lian; Muen Zou; Shun Wang (Materials Today Catalysis)
Graphene-based materials with large specific surface area, strong stability and easy adjustability attract considerable attention in the field of hydrogen storage; however, they suffer from poor hydrogen adsorption ability as direct physical adsorbents or limited modification effect as catalytic supporters of chemical hydrides, blamed to tightly stacked layer structure and chemical inertness. Structural engineering and functional decoration on graphene have been proven to be effective strategies for enhancing both physical and chemical hydrogen storage performances, but there is still lack of simple and flexible method to achieve their synergy. Here for the first time, we develop a fluorine-functionalized intercalated graphene with adjustable layer spacing by one-step solvothermal process, using fluorinated organic molecules as both intercalation and function agents. By the virtue of expanded interlayer and high-electronegative fluorine, it shows polarization-enhanced physisorption ability. Moreover, when using it as the supporter for LiBH4, the operation temperature, reaction kinetics and cyclic stability of the whole system are greatly improved, attributed to the intrinsic catalysis of carbonaceous materials and the destabilization induced by fluorine substitution. This work provides new views for structural and functional co-design in graphene derivate, and brings hope for their practical application for hydrogen storage.